2023
DOI: 10.3390/ijms24021323
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antimicrobial, Antiadhesive and Co-Aggregation Activity of a Multi-Strain Probiotic Composition against Different Urogenital Pathogens

Abstract: The urogenital microbiota is dominated by Lactobacillus that, together with Bifidobacterium, creates a physiological barrier counteracting pathogen infections. The aim of this study was to evaluate the efficacy of a multi-strain probiotic formulation (Lactiplantibacillus plantarum PBS067, Lacticaseibacillus rhamnosus LRH020, and Bifidobacterium animalis subsp. lactis BL050) to inhibit adhesion and growth of urogenital pathogens. The antimicrobial and antiadhesive properties of the probiotic strains and their m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…L. crispatus can decrease the adhesion and invasiveness of N. gonorrhoeae through reducing the expression of genes responsible for pro-inflammatory cytokines like TNF-α and CCL20 in N. gonorrhoeae -infected epithelial cells ( Płaczkiewicz et al., 2020 ). Similarly, the cell surface aggregation-promoting factor from L. gasseri can block Trichomonas vaginalis adhesion to human vaginal ectocervical cells in a dose-dependent manner ( Phukan et al., 2018 ; Malfa et al., 2023 ). The three main intracellular parasites in the female vagina, Mycoplasma , Chlamydia , and Ureaplasma , have also been shown to be inhibited from infecting the vagina by lactate, bacteriocins, and the acidic environment induced by lactobacilli ( Parolin et al., 2018 ; García-Galán et al., 2020 ; Garza et al., 2021 ; Chen et al., 2022 ).…”
Section: Probiotic Lactobacilli In the Treatment Of Vaginal Infectionsmentioning
confidence: 99%
“…L. crispatus can decrease the adhesion and invasiveness of N. gonorrhoeae through reducing the expression of genes responsible for pro-inflammatory cytokines like TNF-α and CCL20 in N. gonorrhoeae -infected epithelial cells ( Płaczkiewicz et al., 2020 ). Similarly, the cell surface aggregation-promoting factor from L. gasseri can block Trichomonas vaginalis adhesion to human vaginal ectocervical cells in a dose-dependent manner ( Phukan et al., 2018 ; Malfa et al., 2023 ). The three main intracellular parasites in the female vagina, Mycoplasma , Chlamydia , and Ureaplasma , have also been shown to be inhibited from infecting the vagina by lactate, bacteriocins, and the acidic environment induced by lactobacilli ( Parolin et al., 2018 ; García-Galán et al., 2020 ; Garza et al., 2021 ; Chen et al., 2022 ).…”
Section: Probiotic Lactobacilli In the Treatment Of Vaginal Infectionsmentioning
confidence: 99%
“…Viable probiotics can interact with pathogen cells by competing for cellular receptor binding and avoiding the cell adhesion of pathogens to human cells [ 35 ]. Malfa and collaborators investigated probiotic co-aggregation with urogenital pathogens, demonstrating that single and mixed Lactobacillus strains could prevent urogenital infections without impairing tissue integrity [ 36 ]. Zakaria et al suggested that quorum sensing signaling molecules could explain the co-aggregation between Lactobacillus probiotics and pathogens, thus contributing to creating barriers that are able to prevent pathogen adhesion to epithelia and tissue invasion, and increasing the host defenses against infections in several districts [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is worth mentioning that LAB exert strain-specific probiotic properties. For example, the antimicrobial and antiadhesive properties of L. plantarum PBS067 and L. rhamnosus LRH020 were already demonstrated in the context of urogenital infections in human bladder epithelia, where the probiotics were able to co-aggregate with urogenital pathogens, limiting the colonization [49].…”
Section: Discussionmentioning
confidence: 99%